Prove that: tan 3A – tan 2A – tan A = tan 3A tan 2A tan A
Answers
=====================================================
Question : Prove that: tan 3A – tan 2A – tan A = tan 3A tan 2A tan A
Answer : tan 3A – tan 2A – tan A = tan 3A tan 2A tan A
Formula : ![tan(A+B)=\frac{tanA+tanB}{1-tanA.tanB} tan(A+B)=\frac{tanA+tanB}{1-tanA.tanB}](https://tex.z-dn.net/?f=tan%28A%2BB%29%3D%5Cfrac%7BtanA%2BtanB%7D%7B1-tanA.tanB%7D)
Step-by-step explanation :
Hence Proved .
=====================================================
>>> Hope Helps You <<<
Given : tan 3A – tan 2A – tan A = tan 3A tan 2A tan A
To find : Prove
Solution:
Tan3A = Tan(2A + A)
as we know that Tan(X + Y) = (TanX + TanY) /(1 - TanXTanY)
X = 2A & Y = A
=> Tan3A = (Tan2A + TanA)/(1 - Tan2A.TanA)
=> (1 - Tan2A.TanA)Tan3A = Tan2A + TanA
=> Tan3A - Tan3A.Tan2A.TanA = Tan2A + TanA
=> Tan3A - Tan2A - TanA = Tan3A.Tan2A.TanA
QED
Hence Proved
Tan3A - Tan2A - TanA = Tan3A.Tan2A.TanA
Learn more :
tanA+cotA=2 then find the value of tan3A+cot3A=? - Brainly.in
https://brainly.in/question/12336068
Cot3A. Sin3A /(cos A+ sinA)2 +tan3A .cos3A /(cosA+sinA)2= secA ...
https://brainly.in/question/14943798
Solve the equation (sec A-2)(tan 3A-1)
https://brainly.in/question/11773291